2019
DOI: 10.1159/000501045
|View full text |Cite
|
Sign up to set email alerts
|

Lung Recruitment Maneuvers for ARDS Patients: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> Lung recruitment maneuvers (LRMs) may reduce mortality and improve oxygenation in patients with acute respiratory distress syndrome (ARDS). However, the existing literature provides controversial conclusions. <b><i>Objectives:</i></b> To determine whether LRMs have benefits on ARDS patients. <b><i>Searching Methods:</i></b> We searched relevant studies in PubMed, EMBASE, Medline, and the Cochrane Library up to May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
0
20
0
2
Order By: Relevance
“…Lung recruitment maneuvers do not significantly reduce mortality but may improve oxygenation and shorten the length of hospital stay in ARDS patients. 42 Overall, recruitment maneuvers are not supported by high-quality evidence, 43 and caution should be exercised when using it because it can be irritating, incite coughing, and generate aerosols.…”
Section: Ventilation Managementmentioning
confidence: 99%
“…Lung recruitment maneuvers do not significantly reduce mortality but may improve oxygenation and shorten the length of hospital stay in ARDS patients. 42 Overall, recruitment maneuvers are not supported by high-quality evidence, 43 and caution should be exercised when using it because it can be irritating, incite coughing, and generate aerosols.…”
Section: Ventilation Managementmentioning
confidence: 99%
“…Nevertheless, some new clinical trials sound promising such as the use of higher positive end-expiratory pressure (Dries, 2019 ). It has also been shown that lung recruitment maneuvers may improve the oxygenation process and shorten the hospital stay period in ARDS (Cui et al., 2020 ) and avoid the pro-inflammatory processes triggered by mechanical ventilation (Spadaro et al., 2019 ) . Because in ARDS, the lung injury is accompanied with an acute onset, the recognition and the determination of the respiratory damage threshold would certainly be a key point for a better and efficient ARDS therapy (Dries, 2019 ).…”
Section: Management and Treatment Strategies Of Ards Associated Sars-mentioning
confidence: 99%
“…that the total amount of lung recruitment tissue increased with ARDS severity [33]. A recent two pairwise meta-analysis suggested that RM had no advantageous effect on mortality [13,34]. Higher PEEP reduced mortality in the subgroup for patients with ARDS who responded to increased PEEP by improved oxygenation; overall, higher PEEP was not an advantageous for patients with ARDS [11].…”
Section: Discussionmentioning
confidence: 99%